Coefficient estimates for certain classes of analytic functions involving the extended q-fractional operator - Alomar, Areej; Maslina Darus,; Alshammari, Khalid M. K. (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this paper, a new extended q-fractional operator using the convolution of the Al-Oboudi differential operator with the q-fractional integral operator J α,τ q f(z) is introduced. The qfractional integral operator J α,τ q f(z) was recently defined and many new results are yet to be studied. From this extended operator, the coefficient problems involving the second Hankel determinant H2 2 f(z) and the Fekete-Szeg¨o theorem are solved.